2006
DOI: 10.1071/ch05338
|View full text |Cite
|
Sign up to set email alerts
|

Studies Towards the Synthesis of Salvinorin A

Abstract: Salvinorin A 1, a psychoactive neoclerodane diterpenoid from the Mexican sage S. divinorum, has gained interest as a selective κ-opioid receptor agonist. Non-racemic 3-furylamines 9a and 9b have been prepared from (+)-pseudoephedrine and (−)-ephedrine for application in the stereoselective synthesis of the ketone ring of 1. Diels-Alder reaction of 9b with methyl acrylate in aqueous media, followed by selective ether bridge cleavage, has allowed access to the cyclohexenone 17 with preservation of stereochemistr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 35 publications
0
14
0
1
Order By: Relevance
“…The first studies toward the total synthesis of 2a were reported by Lingham et al 90 The proposed synthetic route dissected 2a into cyclohexanone 147 and lactone 148 ( Figure 12). It was envisioned that Michael addition followed by olefin metathesis and hydrogenation would afford 2a.…”
Section: Total Synthesis Effortsmentioning
confidence: 99%
“…The first studies toward the total synthesis of 2a were reported by Lingham et al 90 The proposed synthetic route dissected 2a into cyclohexanone 147 and lactone 148 ( Figure 12). It was envisioned that Michael addition followed by olefin metathesis and hydrogenation would afford 2a.…”
Section: Total Synthesis Effortsmentioning
confidence: 99%
“…Synthesis of 12 by Scheerer et al50 Reagents and conditions : (a) propyne, n -BuLi, Et 2 O, −78 °C; (b) ( R )-β-Methyl-CBS catalyst, BH 3 •Me 2 S, −30 °C; (c):(1) KH, H 2 N(CH 2 ) 3 NH 2 , 0 °C; (2) Me 3 Al, Cp- 2 ZrCl 2 , I 2 , −45 °C; (3) TESCl, imidazole; (d) Ni-( R )-BINAP(OTf) 2 , 2,6-lutidine, BF 3 •OEt 2 , HC(OMe) 3 ; (e) HO 2 CCH 2 CO 2 Et, i -PrMgCl, 65 °C ; (f) LiHMDS ; ClPO(OEt) 2 ; (g) Fe(acac) 3 , MeMgCl, −20 °C; (h):(1) DIBAL-H, −78 °C; (2) MnO 2 ; (3) Sn(OTf) 2 , N -ethylpiperidine, chiral auxiliary, −78 °C; (i): (1) TBSOTf, 2,6-lutidine; (2) K 2 CO 3 , CH 3 OH; (3) OsO 4 , NMO, NaIO 4 ; (4) Zn(OTf) 2 , (−)- N -Methyl-ephedrine, Et 3 N, 4-phenyl-1-butyne; (j):(1) BOMCl, NaHMDS, −78 °C; (2) Lindlar catalyst, H 2 ; (3) K 2 OsO 4 , NMO, citric acid, 50 °C, Pb(OAc) 4 , K 2 CO 3 ; (k) 27 , n -BuLi, MgBr•OEt 2 , CH 2 Cl 2 , −78 to 0 °C; (l): (1) TBSOTf, 2,6-lutidine; (2) PPTS, CH 3 OH; (3) LiOH, i -PrOH, H 2 O; (m):(1) MNBA, DMAP, [0.0015 M]; (2) TBAF; (3) Dess-Martin periodinane; (n) TBAF, −78 to 5 °C; (o): (1) NaH, Comins reagent; (2) Pd(OAc) 2 , dppf, Et 3 SiH; (3) L-selectride, t -BuOH, −78 to −55 °C; (p) LiBF 4 , acetonitrile/H 2 O; (q) NaClO 2 , TMSCHN 2 ; (r) K 2 CO 3 , CH 3 OH; (s) Ac 2 O, pyridine, DMAP.…”
Section: Figuresmentioning
confidence: 99%
“…All structural derivatization studies reported to date have involved systematic modification of salvinorin A extracted directly from the leaves of S. divinorum. Several total synthesis efforts have been reported (Lingham et al, 2006;Scheerer et al, 2007;Burns and Forsyth, 2008;Nozawa et al, 2008;Bergman et al, 2009;Hagiwara et al, 2009); however, their time and resource investment, compared with the relative ease in isolation from natural sources, render their application thus far suboptimal for use in SAR development. Binding affinities and functional activities of analogs at MOP, DOP, and KOP receptors are described in Table 1.…”
Section: A Structure-activity Relationships Of Analogsmentioning
confidence: 99%